Escritos narrativos de uma produção desejante com a EMEF EJA Admardo Serafim de Oliveira - Clemente, Ozilene Pereira (2016)
What can a youth and adult education as power differ in a country which still fight for access and permanence in school, where there are vulnerable conditions for the exercise of the right to education? Moved by this question, this research aims to analyze the ethics and desiring production flow with teachers, students, management team and researchers from EMEF EJA Admardo Serafim de Oliveira. For this, we combine the concept of Ethics in Spinoza, through the reading of Deleuze and desire in reading Deleuze, Guattari and Rolnik, which aim to discuss with the production of subjectivity in their catch using technologies of scapegoating, segregation and infantilization that subdues and life segments in power relations. Narratives were produced to express the way the School Admardo in their desiring production generates "short circuit" to this logic, in their daily confrontations. Highlighted, the analysis of continuing education as a space of problematizations, questions and struggles that builds crossed by a political-ethical-aesthetic in asserting lives through a process of educating inventive and artistic. Contrary to some educational logic, teachers, students, management team and researchers from School Admardo struggle and resist for public education in the youth and adults modality.